The hiding hyena / Antonia Ringbom - Ringbom, Antonia; Kiklund, Alison (Estados Unidos de América: Somondoco Press)
Nobody likes me, who wants to play wiwth me?, I´ve heard he´s HIV infected, oh! look at those lovely girls!, we have to find a new home, sister Impala!, hello girls! can I join you?, whats that? no trees!!!, Ugh! more and more coffins ae needed, how can I get impala alone?, cheer up girls!, Mr Lion is sick!. What this deadly disease?, The dangerous disease is called AIDS and is transmitted through blood and sexual contact by the HI-virus, and you boy! abstain from sex with those girls and learn your ABC*!, What is HIV (human inmmunodeficiency virus).
Incluye ilustraciones
Col. Educ.
Keywords: 1. CUENTOS 2. THE HIDING HYENA 3. LITERATURE 4. EDUCATION